Molecular pathways of senescence regulate placental structure and function. (3rd August 2020) - Gal, Hilah; Lysenko, Marina; Stroganov, Sima; Vadai, Ezra; Youssef, Sameh A; Tzadikevitch‐Geffen, Keren; Rotkopf, Ron; Biron‐Shental, Tal; de Bruin, Alain; Neeman, Michal; Krizhanovsky, Valery
Abstract :